Modification of biochar surface by air oxidation: Role of pyrolysis temperature. (February 2016) - Suliman, Waled; Harsh, James B.; Abu-Lail, Nehal I.; Fortuna, Ann-Marie; Dallmeyer, Ian; Garcia-Perez, Manuel
Abstract: This paper reports the effects of pyrolysis temperature on biochar to oxidation by air. Eighteen biochars were produced from the pyrolysis of Douglas fir wood (DFW), Douglas fir bark (DFB), and hybrid poplar wood (HP) at six temperatures (623, 673, 723, 773, 823 and 873 K) in a lab scale spoon reactor. The oxidation step for all biochars produced was conducted at 523 K in the presence of air in a spoon reactor. The elemental and proximate analyses of all the oxidized and un-oxidized chars suggest that the carbonaceous materials produced at low temperature are more susceptible to oxidation than those produced at high temperature. A number of surface properties of resultant biochars were examined to better understand how pyrolysis temperatures and feedstock sources relate to the development of surface characteristics. The removal of volatiles during the pyrolysis step resulted in the gradual creation of microporosity detectable by CO2 adsorption but which was difficult to detect with N2 adsorption, suggesting that the chars contain micropores mostly less than 1 nm in entrance dimension. In some cases, the surface area decreased after being oxidized likely due to the blockage of micropores by oxygen-containing functional groups. The surface composition determined by XPS and Boehm titration confirms that greater quantities of carbonyl and carboxyl groups are formed on biochars produced at low temperature. The formation of these oxygenated functional groups contributes to add negative charges on the surface and consequently the pH at the point of zero charge increases for un-oxidized biochars. Highlights: Oxidizing biochar in air at 250 °C adds carbonyl and carboxyl groups on biochar surfaces. Biochars produced at higher temperatures are more recalcitrant to oxidation. In some cases, the surface area decreased after being oxidized. Oxygenated functional groups contribute to add surface negative charges.